Transport of Swirling Entropy Waves through an Axial Turbine Stator - Andrea Notaristefano; Paolo Gaetani (International Journal of Turbomachinery, Propulsion and Power, 2021)
The transport of entropy waves and their impact on the stage aerodynamics are still open questions. This paper shows the results of an experimental campaign that focuses on the swirling entropy waves advection through an axial turbine stator. The research aims at quantifying the aerodynamic impact of the swirling entropy waves on the first nozzle and characterizing their transport. The disturbance is generated by a novel entropy wave generator that ensures a wide set of different injection parameters. The device injects the disturbance axially, four different clocking positions are investigated. Measurements show a severe temperature attenuation of the swirling entropy wave at stator outlet. The high temperature location changes with the injection position as a result of the different interaction with the stator secondary flows. Depending on the injection position, the aerodynamic flow field is strongly perturbed by the injected swirl profile, instead the entropy wave effect is negligible.